The relationship between severe extracranial artery stenosis or occlusion and cerebral small vessel disease in patients with large artery atherosclerotic cerebral infarction - Dai, Pei; Yu, Hui-xian; Wang, Zhao-xia; Liu, Si-hao; Xu, Guang-qing (Frontiers in Neurology, 2022)
Background and purpose Extracranial artery stenosis (ECAS) is associated with the presence of individual markers of cerebral small vessel disease (CSVD). Here, we investigated the relationship between severe extracranial artery stenosis or occlusion and CSVD in patients with large artery atherosclerotic (LAA) cerebral infarction. Methods A total of 128 patients with LAA cerebral infarction who met our specific inclusion criteria were selected, including 92 males and 36 females. These patients were divided into three groups based on whether they had severe symptomatic extracranial arterial stenosis or occlusion, severe asymptomatic extracranial artery stenosis or occlusion, or severe extracranial artery stenosis or occlusion (both symptomatic and asymptomatic). Intra-group comparisons were then performed to examine whether there were any differences in the total CSVD scores and Fazekas scores. Results Patients with severe extracranial arterial stenosis or occlusion and those with severe asymptomatic extracranial arterial stenosis or occlusion had a significantly higher total CSVD score (P < 0.05), but there were no significant differences between the groups in terms of Fazekas scores. Furthermore, there were no significant difference in the total CSVD scores and Fazekas scores when compared between patients with or without severe symptomatic extracranial arterial stenosis or occlusion. Conclusion Severe stenosis or occlusion of the contralateral extracranial artery may increase the incidence of CSVD in patients with LAA cerebral infarction. Active and effective clinical intervention following comprehensive evaluation should be undertaken for unilateral cerebral infarction patients with severe stenosis or occlusion of the contralateral extracranial arterial.